Empirical errors and predicted errors in fertility, mortality and migration forecasts in the European Economic Area - Nico Keilman; Dinh Quang Pham (Statistics Norway, Research Department, 2004)
We analyse empirical errors observed in historical population forecasts produced by statistical agencies in 14 European countries since 1950. The focus is on forecasts for three demographic variables: fertility (Total Fertility Rate - TFR), mortality (life expectancy at birth), and migration (net migration). We inspect forecast bias and forecast accuracy in the historical forecasts, as well as the distribution of the errors. Finally, we analyse for each of the three variables correlation patterns in forecast errors across countries and, for mortality, the correlation between errors for men and women. In the second part of the report we use time series model to construct prediction intervals to 2050 for the TFR, the life expectancy for men and women, and net migration in 18 European countries. GARCH models are used for fertility and mortality, while net migration is modelled as an autoregressive process
Keywords: C22; J11; 330; stochastic population forecast; empirical forecast errors; prediction intervals; GARCHmodels; TFR; life expectancy; net migration; EEA